1997
DOI: 10.1097/00000539-199712000-00039
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Anesthetic Maintenance Technique Influences the Antiinflammatory Cytokine Response to Abdominal Surgery

Abstract: This study demonstrates that in addition to the widely reported proinflammatory cytokine response, elective abdominal surgery provokes an antiinflammatory response, which may be enhanced by total intravenous anesthesia. The ability of anesthetics to modify the cytokine response to surgery may have therapeutic potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…The enhanced release of IL-10 after surgery in patients receiving general anesthesia possibly reflects the reaction to limit a proinflammatory response or may be a result of direct effects of propofol and fentamyl on IL-10 producing cells. Gilliland et al (1997) also found increased levels of IL-10 and IL-1Ra postoperatively in patients receiving intravenous anesthesia with propofol and alfetanil and concluded about an enhanced anti-inflammatory response by i.v. anesthesia.…”
Section: Discussionmentioning
confidence: 92%
“…The enhanced release of IL-10 after surgery in patients receiving general anesthesia possibly reflects the reaction to limit a proinflammatory response or may be a result of direct effects of propofol and fentamyl on IL-10 producing cells. Gilliland et al (1997) also found increased levels of IL-10 and IL-1Ra postoperatively in patients receiving intravenous anesthesia with propofol and alfetanil and concluded about an enhanced anti-inflammatory response by i.v. anesthesia.…”
Section: Discussionmentioning
confidence: 92%
“…8,9,20,21 The type of anesthesia may also have a role by influencing the inflammatory cytokine response. 22 As most of the patients worldwide are operated on under general anesthesia, to avoid any possible bias all patients in this study were operated on under general anesthesia. In the present study the contrast media used as well as the aneurysm's thrombus load were not correlated with PIS.…”
Section: Discussionmentioning
confidence: 99%
“…An important goal of current anesthetic research is to find the "stress-free anesthetic method" that can limit activation of the neuroendocrine, inflammatory, and immune responses [12,13]. Many studies suggest that the choice of anesthetic technique can influence the stress response by stimulating, inhibiting, or modulating the pathophysiologic pathways that cause neurohumoral and immunologic changes [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that the choice of anesthetic technique can influence the stress response by stimulating, inhibiting, or modulating the pathophysiologic pathways that cause neurohumoral and immunologic changes [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%